The year without Mardi Gras: the New Orleans Police Strike of 1979 - Bovenkerk, Frank (Crime, law and social change, 1993)
This is a case study of the proceeding of one police strike in the American Deep South of the 1970s. The author discusses the strike as a conflict between the Teamsters' Union wanting to make an inroad among governmental workers in major cities and a just elected black city administration. The threat that organized crime would take over turned against the local Police Union as Northern so-called international negotiators had been brought to New Orleans. First black mayor "Dutch" Morial was supported by the captains of the Mardi Gras parades to call off Mardi Gras in order to break the strike.